2012
DOI: 10.1103/physrevlett.109.097603
|View full text |Cite
|
Sign up to set email alerts
|

Structural Heterogeneity and Diffuse Scattering in Morphotropic Lead Zirconate-Titanate Single Crystals

Abstract: Complementary diffuse and inelastic synchrotron x-ray scattering measurements of lead zirconate-titanate single crystals with composition near the morphotropic phase boundary (x=0.475) are reported. In the temperature range 293 K Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…S1). Static diffuse scattering was recently reported in a single crystal of PZT with x = 0:475 using X-ray inelastic scattering techniques (41). However, these data were obtained with an energy resolution nearly 10 times coarser than ours; hence there is a possibility of phonon contamination.…”
Section: Resultsmentioning
confidence: 46%
“…S1). Static diffuse scattering was recently reported in a single crystal of PZT with x = 0:475 using X-ray inelastic scattering techniques (41). However, these data were obtained with an energy resolution nearly 10 times coarser than ours; hence there is a possibility of phonon contamination.…”
Section: Resultsmentioning
confidence: 46%
“…However, although there has been some published work regarding the real local structures of PZT [30][31][32][33][34][35] , most lack a thorough analysis of the role of the Pb atoms in the MPB area. Here, PDF analyses of PZT compositions with x ¼ 0.2, 0.3 and 0.4 are presented and a re-examination of earlier Rietveld results show that the displacements of the Pb atoms undergo a composition-enforced change between two monoclinic variants, thus revealing a monoclinic-monoclinic boundary (crossover) for the first time.…”
mentioning
confidence: 99%
“…However some authors reported that the true ground state of PZT in and around the MPB is rhombohedral in the R3c space group and it coexists with the monoclinic phase in Cm space group over a wide composition range [14][15][16][17][18][19][20] . Thus the true symmetry of the low temperature phase of PZT has become controversial as evidenced by several recent publications on this system [17][18][19][20][21][22][23] . The main objection against the Cc space group is the non-observation of the (1/2 1/2 1/2) pc (pc stands for pseudocubic indices) superlattice peak which is permitted by the Cc space group but is extinguished in the R3c space group.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the low-temperature superlattice phase in the Cc space group was confirmed by other workers also in their transmission electron microscopy (TEM) 11,12 and neutron powder diffraction studies as a function of temperature 10,13 and pressure 13 and was nearly accepted as the true ground state of PZT. However some authors reported that the true ground state of PZT in and around the MPB is rhombohedral in the R3c space group and it coexists with the monoclinic phase in Cm space group over a wide composition range [14][15][16][17][18][19][20] . Thus the true symmetry of the low temperature phase of PZT has become controversial as evidenced by several recent publications on this system [17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
See 1 more Smart Citation